Frequency, associated factors, and outcome of raised intraocular pressure in live-related renal transplant recipients: a single-centre experience - Lanewala, Fatema Ali; Akhtar Jamal Khan; Mirza Naqi Zafar; Tahir Aziz (Journal of the Pakistan Medical Association, 2025)
Objective: To investigate the frequency, associated factors and outcomes of elevated intraocular pressure in live-related renal transplant recipients. Method: The study was conducted at the Department of Ophthalmology, Sindh Institute of Urology and Transplantation, Karachi, in 2023. The data was divided into group A cases having intraocular pressure >23mmHg and group B controls having intraocular pressure <23mmHg. The groups were compared for factors such as immunosuppression medications, acute rejection episodes, human leukocyte antigen match, duration of dialysis before transplant, and pre-existing microvascular diseases. Data was analysed using SPSS 22. Results: Of the 2,738 patients screened, 131(4.8%) exhibited intraocular pressure >23mmHg. Intergroup comparison between group A and group B showed no significant relationship of intraocular pressure increase with cyclosporine, tacrolimus and everolimus (p>0.05). Azathioprine demonstrated significant association with intraocular pressure elevation at the time of measuring intraocular pressure (p<0.05). Mycophenolate mofetil showed an association with IOP only when assessed as initial immunesuppression at the time of transplantation (p<0.05). At the time of IOP assessment, MMF was not found to be a significant factor responsible for IOP elevation (p>0.05). Patients who had received Antithymocyte globulin (ATG) were found to have remarkable association with raised IOP. No significant link was noted between hypertension, dialysis duration and human leukocyte antigen match (p>0.05). The multivariate analysis showed that Azathioprine was the only factor associated with raised IOP at the time of assessment (p<0.001) Conclusion: There was a potential risk of medication side effects, including secondary glaucoma, among renal transplant recipients. Key Words: Renal transplant, Steroids, Intraocular pressure, Glaucoma.